Strategi Peningkatan Hasil Ujian Nasional di SMP Al Irsyad Al Islamiyyah Purwokerto Tahun Pelajaran 2016/2017 - Machfudh Fathoni (Jurnal Kependidikan, 2017)
National Examination is one of the indicators of school quality. Therefore, efforts to improve the national exam results are important for schools as part of quality assurance. This study aims to find out the strategy of SMP Al Irsyad Al Islamyyah Purwokerto in improving the results of National Examination. This is a qualitative study with a case study approach. Source of the data are informants and document archives. Data were obtained through interview and documentation and their validity was achieved through triangulation of source. Steps of data analysis were data reduction, data presentation and verification. The results of this study indicate that: (1) The strategy in improving the results of national examination conducted by SMP Al Irsyad has been good enough, covering academic fields (academic matriculation, afternoon tutoring, try out, intensive study guidance, peer tutor and night study) and non-academic field (commitment day, inviting inspirative figures, fun class managers, out bond and prayer together before the National Examination); (2) Optimal implementation of strategies that have been arranged; (3) The obstacles related to improving the national exam results are: students' boredom, students' different characters, and weather conditions.